Solar Biomass Gasification Combined With Iron Oxide Reduction for Syngas Production and Green Iron Metallurgy - Bellouard, Quentin; Rodat, Sylvain; Grateau, Maguelone; Abanades, Stéphane (Frontiers in Energy Research, 2020)
The solar gasification of biomass with iron oxide for combined syngas and iron production was investigated. Both solar energy and biomass are promising renewable energies. The process of gasification converts solid carbonaceous feedstocks into either fuels or chemicals. However, conventional processes require partial combustion of the feedstock for energy supply and inherently suffer from high oxygen production costs and low syngas calorific value due to dilution with combustion products. Chemical looping gasification using solid oxides is an alternative option to tackle these issues. By supplying concentrated solar energy as the high-temperature heat source, it is possible to produce even more syngas from the process while enabling solar energy storage into dispatchable fuels. This work proposes to explore solar biomass gasification over iron oxide at high heating rates, representative of the conditions obtained in solar reactors. Thermodynamic equilibriums of gasification reactions between 100 and 1,500°C were calculated and experimental results obtained at 1,100°C with a specially designed induction furnace were reported for biomass gasification with iron oxide, water, or carbon dioxide as oxidizing agents. Solid products analysis showed that iron oxide can be reduced to metallic iron depending on the proportion of the oxygen carrier. These results indicate that iron oxide is an effective material for solar biomass gasification producing both syngas and iron via a novel green metallurgical process.